High-resolution slow-motion sequencing how to generate a slow-motion sequence from a bit stream. - Chaudhuri, S. (IEEE Signal processing magazine)
Video surveillance is one of the applications where high-resolution (HR) images are crucial. The frames need to be super resolved to obtain an HR description of the scene and must be replayed at a relatively slow speed. HR slow-motion sequencing refers to the task of creating an HR slow-motion video from a given video bit stream. A better visual quality of slow video sequence can be obtained by applying the HR slow-motion sequencing algorithm to any given low-resolution (LR) video sequence. This article presents a tutorial concept demonstration type. It describes the image acquisition model utilized by the super resolution (SR) technique. The article also explains the general methodology used by the existing video compression standards to see how the existing SR techniques exploit the bit stream information to obtain the HR sequence. The authors also describe the method employed in obtaining the HR slow-motion sequences and demonstrate the results of the developed algorithm for surveillance videos.